2015
DOI: 10.3945/jn.115.210823
|View full text |Cite
|
Sign up to set email alerts
|

Higher Maternal Plasma n–3 PUFA and Lower n–6 PUFA Concentrations in Pregnancy Are Associated with Lower Childhood Systolic Blood Pressure

Abstract: Higher maternal plasma n-3 PUFA and lower n-6 PUFA concentrations during pregnancy are associated with a lower systolic blood pressure in childhood. Further studies are needed to replicate these findings, explore the underlying mechanisms, and examine the long-term cardiovascular consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“… 13 Some of us began measuring childhood BP in 2010 as part of monitoring the overall health of children born to women in the KUDOS trial and because a report of early postnatal DHA supplementation 5 linked lower BP at age 6 years to higher DHA exposure. Subsequent reports from the Netherlands 3 , 4 associating prenatal DHA exposure with lower childhood BP supported our hypothesis that children of women randomized to DHA supplementation would have lower BP.…”
Section: Discussionsupporting
confidence: 68%
“… 13 Some of us began measuring childhood BP in 2010 as part of monitoring the overall health of children born to women in the KUDOS trial and because a report of early postnatal DHA supplementation 5 linked lower BP at age 6 years to higher DHA exposure. Subsequent reports from the Netherlands 3 , 4 associating prenatal DHA exposure with lower childhood BP supported our hypothesis that children of women randomized to DHA supplementation would have lower BP.…”
Section: Discussionsupporting
confidence: 68%
“…However, no correlations between maternal dietary factors and childhood blood pressure were found to be statistically significant (412). On the other hand, another study found that higher total maternal n-3 PUFA levels were associated with lower childhood systolic blood pressure (419). These studies illustrate the potential for maternal serum markers, whether placental, hormonal, or dietary, to be predictive of adult later-life hypertension in their children, an area which warrants further investigation.…”
Section: Prediction Of Developmental Programmingmentioning
confidence: 88%
“…Increased concentrations of free fatty acids during pregnancy are associated with childhood obesity [ 41 , 42 ]. Previously, we have shown that higher maternal n-3 PUFA and lower n-6 PUFA concentrations in pregnancy are also associated with lower childhood systolic blood pressure [ 43 ].…”
Section: Discussionmentioning
confidence: 99%